2021
DOI: 10.3390/ma14216347
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Microstructure Induced by Surface Mechanical Attrition Treatment in Grade 2 Titanium Studied Using Positron Annihilation Spectroscopy and Complementary Methods

Abstract: Microstructural changes in grade 2 titanium generated by surface mechanical attrition treatment (SMAT) were studied using positron annihilation lifetime spectroscopy and complementary methods. A significant increase in the mean positron lifetime indicated many lattice defects introduced by SMAT. Two positron lifetime components were resolved in the positron lifetime spectra measured. The longer lifetime revealed the presence of vacancy clusters containing about 3 or 4 vacancies, while the shorter one was attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…He et al [26] investigated changes in the microstructure of four batches of welded SMA490BW steel specimens treated with different ultrasonic impact treatment parameters, and the gradient microstructure became more obvious as the thickness of the plastic deformation zone increased. Although not as common as in workpieces treated with SMRT and UNSM, some researchers also observed a clear gradient microstructure on other selected titanium and steel workpieces after treatment with the appropriate SP, SMAT, and LSP methods [40][41][42][43]. Nevertheless, these studies did not investigate the effects of SP, SMAT, and LSP-induced gradient microstructure on the very-high-cycle fatigue properties of the selected metals; therefore, these may still be potential areas for future studies.…”
Section: Plastic Deformation Zone Nanograin Layer and Gradient Micros...mentioning
confidence: 96%
“…He et al [26] investigated changes in the microstructure of four batches of welded SMA490BW steel specimens treated with different ultrasonic impact treatment parameters, and the gradient microstructure became more obvious as the thickness of the plastic deformation zone increased. Although not as common as in workpieces treated with SMRT and UNSM, some researchers also observed a clear gradient microstructure on other selected titanium and steel workpieces after treatment with the appropriate SP, SMAT, and LSP methods [40][41][42][43]. Nevertheless, these studies did not investigate the effects of SP, SMAT, and LSP-induced gradient microstructure on the very-high-cycle fatigue properties of the selected metals; therefore, these may still be potential areas for future studies.…”
Section: Plastic Deformation Zone Nanograin Layer and Gradient Micros...mentioning
confidence: 96%
“…Huang et al reported that the passive film resistance (R p ) of SMAT-Ti was considerably higher than that of non-treated Ti counterparts in both physiological saline (PS) and simulated body fluid (SBF) solutions [ 79 ]. Moreover, compared with smooth Ti, the grain sizes and boundaries were changed more significantly on roughened Ti after SMAT; hence, SMAT was more effective in enhancing the corrosion resistance of roughened Ti implants [ 80 ]. It is also indicated that remodeling the grain size could thicken the superficial TiO 2 layer on Ti implants by SMAT, establishing a more stable protective layer against chemical corrosion [ 80 ].…”
Section: Enhancing Corrosion Resistancementioning
confidence: 99%
“…Moreover, compared with smooth Ti, the grain sizes and boundaries were changed more significantly on roughened Ti after SMAT; hence, SMAT was more effective in enhancing the corrosion resistance of roughened Ti implants [ 80 ]. It is also indicated that remodeling the grain size could thicken the superficial TiO 2 layer on Ti implants by SMAT, establishing a more stable protective layer against chemical corrosion [ 80 ].…”
Section: Enhancing Corrosion Resistancementioning
confidence: 99%